2016
DOI: 10.1007/s10900-016-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Acceptability of Self-Sampling Kits, Prevalence, and Risk Factors for Human Papillomavirus Infection in American Indian Women

Abstract: We evaluated the feasibility and acceptability of self-sampling for human papillomavirus (HPV) testing and calculated the prevalence of and risk factors for high-risk (hr) HPV infections in a community-based sample of American Indian women. To this end, we recruited 329 Hopi women aged 21-65 years to self-collect vaginal samples for hrHPV testing. Samples were tested by polymerase chain reaction for 14 hrHPV genotypes. We used chi-square tests to identify correlates of preference for clinician Pap testing vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 42 publications
4
42
0
Order By: Relevance
“…Recent evidence suggests that vaginal self‐obtained samples provide sensitivity and specificity equal to clinician‐collected specimens for detecting high‐risk HPV types and cervical intraepithelial neoplasia 2+ . HPV self‐testing acceptability, feasibility and satisfaction studies among Indigenous and ethnic minority women found that HPV self‐testing is preferable to cervical cytology, and potentially eliminates barriers to cervical screening …”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that vaginal self‐obtained samples provide sensitivity and specificity equal to clinician‐collected specimens for detecting high‐risk HPV types and cervical intraepithelial neoplasia 2+ . HPV self‐testing acceptability, feasibility and satisfaction studies among Indigenous and ethnic minority women found that HPV self‐testing is preferable to cervical cytology, and potentially eliminates barriers to cervical screening …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, receptivity by women who actually performed self-sampling is high in other countries [26], and about 90% of women who perform self-sampling also have a positive impression of the use of the self-sampling kits in our study. In addition, it is clarified that 97.4% of the subjects prefer self-sampling to sampling by a clinician and this is higher than (62.0%) in a survey performed by Winer et al [19],clarifying that young Japanese women strongly prefer self-sampling compared with women in other countries.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, there was no social harm or adverse events recorded in previous studies. However, there is a lack of studies that discussed awareness, preference, recognition/perception, and anxiety of women to self-sampling [17][18][19][20][21]. In a previous study of a community-based Canadian women, there was not a significant difference of preference between a Pap smear test performed by clinician or selfsampling, although they indicated a preference of self-sampling, due to comfort and personal feelings [22].There is no other study on the reasons of young women wanting or not wanting to perform selfsampling.…”
mentioning
confidence: 99%
“…In comparison to Pap tests it was seen as a positive experience which women were happy to repeat and recommend to others, also documented in numerous self-sampling trials. [18][19][20][21] Importantly, women mentioned they would not have participated in screening had this not been available.…”
Section: Discussionmentioning
confidence: 99%